Impact of Anxiety and Depression on Student‟s Efficiency and Academic Performance: Addressing the impact of anxiety and depression on students' well-being and academic success (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Students' anxiety and despair are becom ing a serious issue in the classroom. Youthdepression and anxiety are on the rise every year. According to the Anxiety and Depression Association ofAmerica, 1 in 8 youngsters experience anxiety (ADAA). Despite the availability of effective medications,only 20 of children with depression and 80 of children with anxiety disorders actually get therapy.School may be more of a source of anguish than of learning and joy for the many children and adolescentswho suffer from untreated anxiety or depression. Untreated anxiety and depression in students putsthem at risk for a variety of social and behavioral issues as well as academic failure, a lack of interest inpersonal cleanliness and health, and a general lack of confidence.